Factors influencing membership uptake of National Hospital Insurance Fund among the poor : a pastoralist’ perspective - Kipaseyia, John Saitoti (Strathmore University, 2016)
It’s important to address disparities in access to health insurance among marginalized groups in order to accelerate the achievement of Sustainable Development Goals (SDGs) post-2015 and also to identify interventions that will mitigate this situation. The purpose of the study was to establish determinants of uptake of National Hospital Insurance Fund scheme by an informal pastoralist’s community in Kenya, which will be of significance to the government of Kenya in formulating and implementing health insurance policy as it gears towards universal health coverage. The target population was the informal sector participants at Olkeri Group Ranch, Kajiado West Constituency in Kajiado County. Descriptive study design was adopted while simple random sampling method was applied to select a representative sample of 246 households in the study population. The data collection tools were questionnaires with both closed and open ended questions which were reviewed, cleaned and coded to minimize errors and enable easy entry and analysis. Statistical Package for Social Sciences (SPSS) version 20 was used to organize the data and carry out statistical analysis. In the findings only 2.3% of respondents were enrolled in NHIF scheme. This study recommends decision makers modify NHIF policies in terms of reviewing payments of health insurance premiums to ensure those who are still excluded due to lack of cash to pay are brought on board by paying premium in kind using their biological assets. The scheme should also tailor its marketing strategies to cater for those with less or no education by conducting information, education and communication campaigns to promote awareness and knowledge of health insurance.
A research dissertation submitted in partial fulfillment of the requirements for the award of the degree Master of Business Administration-Healthcare Management
Keywords: National Hospital Insurance Fund; Pastoralists; Insurance; Medical insurance